A computing curriculum wiki : analysis and modelling using the MAS-CommonKADS agent-oriented methodology. - Tang, Adelina *; Lee, Angela Siew Hoong * (Sunway University College, 2010)
Curriculum development, maintenance and management are time-consuming and labour-intensive activities resulting from countless feedback-rework cycles. The frequency of such activities tends to increase owing to the accelerated nature of advances in Computing. It is proposed that an existing Computing Ontology be adapted to facilitate these activities by developing a common vocabulary for all Computing disciplines to realize an online Curriculum Wiki facility. The operations of the Wiki would be implemented through ontological agents. This article presents insights into the modelling process of various user-initiated Wiki tasks using the MAS-CommonKADS Agent-Oriented Methodology.